Macromolecular HPMA-based nanoparticles with cholesterol for solid-tumor targeting: detailed study of the inner structure of a highly efficient drug delivery system - Filippov, Sergey K; Chytil, Petr; Konarev, Petr V; Dyakonova, Margarita; Papadakis, Christinem; Zhigunov, Alexander; Plestil, Josef; Stepanek, Petr; Etrych, Tomas; Ulbrich, Karel; Svergun, Dmitri I (Biomacromolecules, 2012)
We report a rigorous investigation into the detailed structure of nanoparticles already shown to be successful drug delivery nanocarriers. The basic structure of the drug conjugates consists of an N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer bearing the anticancer drug doxorubicin (Dox) bound via a pH-sensitive hydrazone bond and a defined amount of cholesterol moieties that vary in hydrophobicity. The results show that size, anisotropy, and aggregation number N(aggr) of the nanoparticles grows with increasing cholesterol content. From ab initio calculations, we conclude that the most probable structure of HPMA copolymer-cholesterol nanoparticles is a pearl necklace structure, where ellipsoidal pearls mainly composed of cholesterol are covered by a HPMA shell; pearls are connected by bridges composed of hydrophilic HPMA copolymer chains. Using a combination of techniques, we unambiguously show that the Dox moieties are not impregnated inside a cholesterol core but are instead uniformly distributed across the whole nanoparticle, including the hydrophilic HPMA shell surface.
Keywords: molekulární konformace; neutronová difrakce; Models, Molecular; micely; Cholesterol; Molecular Conformation; nanokapsle; Macromolecular Substances; Algorithms; cholesterol; světlo; Hydrophobic and Hydrophilic Interactions; doxorubicin; Doxorubicin; Micelles; makromolekulární látky; molekulární modely; velikost částic; Light; Acrylamides; akrylamidy; anizotropie; Nanocapsules; difrakce rentgenového záření; X-Ray Diffraction; Scattering, Small Angle; algoritmy; Antibiotics, Antineoplastic; Neutron Diffraction; maloúhlový rozptyl; Particle Size; Anisotropy; hydrofobní a hydrofilní interakce; protinádorová antibiotika